Vodenje za učenje kot dejavnik razvoja osnovne šole - Pevec, Marija (Vodenje v vzgoji in izobraževanju, 2013)
The article deals with views and perspectives of teachers with reference to leadership for learning in everyday school practice. The first part briefly introduces the theoretical platform about the importance and the role of a leader in the context of leadership for learning in schools. It is based on research results and theoretical guidelines of professionals in the field of leadership for learning. The second empirical part presents the views of teachers on leadership for learning at a selected primary school and in terms of a qualitative approach. The research confirms the significant influence of the head teacher on the process of learning on four levels: the level of teachers, pupils, parents and school as a learning community.
Keywords: culture of learning; head teachers; leadership for learning; learning; ravnatelji; teachers; učenje; učitelji; vodenje